Rethinking "community" relationally: Polish communities in Scotland before and after Brexit. Issue 4 (24th May 2018) - Botterill, Kate
Abstract : Community is a nebulous, contested concept in geography spanning research on social networks, encounters, mobilities, citizenship and belonging. However, its use as a discursive trope in public, policy and academic work points to continued relevance as an analytical category, particularly as meanings of community in Europe are being tested by Brexit. This paper combines diverse scholarship on the geographies of encounter, mobility and citizenship to revisit the concept of "community" using a relational lens. This is explored through an original empirical analysis of the community practices of Polish nationals in Scotland in the context of Brexit. Using biographical‐narrative data collected before and after the UK referendum on EU membership, the paper discusses three forms of community practised by Polish nationals: community centre, a cyber community and a community festival. I advance a relational perspective on community that overcomes spatially and temporally rigid dichotomies of communal experience, emphasising community as a dynamic, interconnected and power‐laden process involving multiple temporalities.